-38-4a=-4-7(-7a+8)

Simple and best practice solution for -38-4a=-4-7(-7a+8) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -38-4a=-4-7(-7a+8) equation:


Simplifying
-38 + -4a = -4 + -7(-7a + 8)

Reorder the terms:
-38 + -4a = -4 + -7(8 + -7a)
-38 + -4a = -4 + (8 * -7 + -7a * -7)
-38 + -4a = -4 + (-56 + 49a)

Combine like terms: -4 + -56 = -60
-38 + -4a = -60 + 49a

Solving
-38 + -4a = -60 + 49a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-49a' to each side of the equation.
-38 + -4a + -49a = -60 + 49a + -49a

Combine like terms: -4a + -49a = -53a
-38 + -53a = -60 + 49a + -49a

Combine like terms: 49a + -49a = 0
-38 + -53a = -60 + 0
-38 + -53a = -60

Add '38' to each side of the equation.
-38 + 38 + -53a = -60 + 38

Combine like terms: -38 + 38 = 0
0 + -53a = -60 + 38
-53a = -60 + 38

Combine like terms: -60 + 38 = -22
-53a = -22

Divide each side by '-53'.
a = 0.4150943396

Simplifying
a = 0.4150943396

See similar equations:

| 81x^4-49x^2= | | 5x-55/4x | | 19=1/2(x)+5 | | 7x+6=83 | | sin^2(x)+2=3*sin(x) | | 3*(2x-1)=4x-9 | | -9+2u=u | | x-4/7=1/3 | | 20x+12=92 | | 2.67=(x/100)*2 | | 21763=974x+15910 | | 4+x^2= | | -22n-2=65 | | 2b=b+6 | | 2(9x+9)=6(3x+3) | | 2x+7+x-6=100 | | 2x+1=5x-35 | | 10+v=-4v | | c=2*3.16*r | | 7x-5y+4=0 | | 4h-3+9=22 | | 2x=4028 | | 8n-2-8= | | 3/5x-9=6 | | 3+8z+z^2=0 | | 2(7v+1)=-14-2v | | .5/y=.02 | | 19=0.5x+5 | | (2x+1)=4(x-3) | | 32+5r=-8(-1-r) | | 17g-16g+1=14 | | 7x+1-4x=4x-5+1 |

Equations solver categories